Quality and Quantity of Protein in Certain Kinds of Edible Mushroom in Thailand - Yaovadee Cuptapun; Duangchan Hengsawadi; Wanpen Mesomya; Sompoch Yaieiam (Agriculture and Natural Resources, 2010)
The chemical composition and nutritional value were determined in four edible mushroom species from Thailand, namely Nang Rom mushroom (Pleurotus sajorcaju) Pao Heo mushroom (Pleurotus ostreatus) Hom mushroom or Shitake (Lentinus edodes) and Kra dang mushroom (Lentinus lepidus). Protein, fat, crude fiber and carbohydrate were 19.59-24.68, 0.25-1.42, 12.29-18.52 and 49.42-55.42% dry weight, respectively. The corrected protein efficiency ratio (C-PER), net protein utilization (NPU), biological value (BV) and true digestibility (TD) were 0.03-1.29, 30.32-40.20, 63.72-77.18 and 47.32-52.16, respectively, compared to values in casein of 2.50, 75.27, 85.98 and 87.49, respectively. Amino acid analysis showed that the protein contained nutritionally useful quantities of essential amino acids, while tryptophan was the limiting amino acid in all the samples. The protein digestibility corrected amino acid score (PDCAAS) of the four mushroom species ranged between 0.32 and 0.45. The results showed that the Hoom mushroom or Shitake had better nutritional protein qualities than the other species studied.